Electrophile-induced conformational switch of the human trpa1 ion channel detected by mass spectrometry - Moparthi, Lavanya; Kjellström, Sven; Kjellbom, Per; Filipovic, Milos; Zygmunt, Peter M.; Johanson, Urban (International Journal of Molecular Sciences, 2020)
The human Transient Receptor Potential A1 (hTRPA1) ion channel, also known as the wasabi receptor, acts as a biosensor of various potentially harmful stimuli. It is activated by a wide range of chemicals, including the electrophilic compound N-methylmaleimide (NMM), but the mechanism of activation is not fully understood. Here, we used mass spectrometry to map and quantify the covalent labeling in hTRPA1 at three different concentrations of NMM. A functional truncated version of hTRPA1 (Δ1-688 hTRPA1), lacking the large N-terminal ankyrin repeat domain (ARD), was also assessed in the same way. In the full length hTRPA1, the labeling of different cysteines ranged from nil up to 95% already at the lowest concentration of NMM, suggesting large differences in reactivity of the thiols. Most important, the labeling of some cysteine residues increased while others decreased with the concentration of NMM, both in the full length and the truncated protein. These findings indicate a conformational switch of the proteins, possibly associated with activation or desensitization of the ion channel. In addition, several lysines in the transmembrane domain and the proximal N-terminal region were labeled by NMM, raising the possibility that lysines are also key targets for electrophilic activation of hTRPA1.
CRIS-Team Scopus Importer:2020-09-18
Keywords: Alkylated thiols; Electrophile sensing; Iodoacetamide; Mass spectrometry; N-methylmaleimide; Pain; Redox sensitivity; TRP channel; TRPA1; Wasabi receptor